Targeted Full Energy and Protein Delivery in Critically Ill Patients: A Pilot Randomized Controlled Trial (FEED Trial). Issue 8 (27th April 2018) - Fetterplace, Kate; Deane, Adam M.; Tierney, Audrey; Beach, Lisa J.; Knight, Laura D.; Presneill, Jeffrey; Rechnitzer, Thomas; Forsyth, Adrienne; Gill, Benjamin M. T.; Mourtzakis, Marina; MacIsaac, Christopher
Abstract: Background: International guidelines recommend greater protein delivery to critically ill patients than they currently receive. This pilot randomized clinical trial aimed to determine whether a volume‐target enteral protocol with supplemental protein delivered greater amounts of protein and energy to critically ill patients compared with standard care. Methods: Sixty participants received either the intervention (volume‐based protocol, with protein supplementation) or standard nutrition care (hourly‐rate‐based protocol, without protein supplementation) in the intensive care unit (ICU). Coprimary outcomes were average daily protein and energy delivery. Secondary outcomes included change in quadriceps muscle layer thickness (QMLT, ultrasound) and malnutrition (subjective global assessment) at ICU discharge. Results: Mean (SD) protein and energy delivery per day from nutrition therapy for the intervention were 1.2 (0.30) g/kg and 21 (5.2) kcal/kg compared with 0.75 (0.11) g/kg and 18 (2.7) kcal/kg for standard care. The mean difference between groups in protein and energy delivery per day was 0.45 g/kg (95% CI, 0.33–0.56; P < .001) and 2.8 kcal/kg (95% CI, 0.67–4.9, P = .01). Muscle loss (QMLT) at discharge was attenuated by 0.22 cm (95% CI, 0.06–0.38, P = .01) in patients receiving the intervention compared with standard care. The number of malnourished patients was fewer in the intervention [2 (7%) vs 8 (28%); P = .04]. Mortality and duration of admission were similar between groups. Conclusions: A high‐protein volume‐based protocol with protein supplementation delivered greater amounts of protein and energy. This intervention was associated with attenuation of QMLT loss and reduced prevalence of malnutrition at ICU discharge.